Curved graphitic nanosheets with single-atom Zn − N4 defects within closed-pores assisting sodium ion nucleation for high-efficiency sodium storage - Shuocong Duan; Dandan Wang; Chi Chen; Tong Xiao; Run Ren; Linan Wang; Wenjie Zhang; Yunfeng Chao; Jianhua Zhu; Xinwei Cui (Chemical Engineering Journal, 2026)

The pharmacokinetics and its covariates of rituximab in different clinical populations: a systematic review and narrative synthesis - Bo Zhenyan; Liang Huang; Jiayi Lu; Zhe Chen; Zhimei Jiang; Linan Zeng; Yuhong Tao; Lingli Zhang (European Journal of Clinical Pharmacology, 2026)

Cytological and molecular genetic evidence of feminized male gametophyte in the brown alga Saccharina japonica - Xiufeng Zhou; Cailing Yi; Nianchao Xue; Yan Li; Juan Sun; Shuxiu Chen; Yuting Zhai; Liang Shi; Yanling Liu; Nan Zhao; Xia Li; Xiaojie Li; et al. (Algal Research, 2026)

Orange-emissive nitrogen doped carbon dots as fluorescent for rapid sensing Ag+ in food water and soil - Dehong Xu; Siqi Chen; Linan Zhou; Fang Zhang; Huiyi Yang; Liangzi Cao; Rongxin Tan; Fang Chai (Journal of Environmental Chemical Engineering, 2026)

Metagenomic and culture-based genomics reveal virulence and resistance risks in Manila clam microbiomes - Yaling Wang; Linan He; Xing Hu; Yuhan Guan; Xiangnan Chen; Jiahui Du; Jiayan Chen; Chensheng Ma; Lianwei Ye (Food Microbiology, 2026)

A single PCR-based sex marker, Sj-SexI, from conserved SDR gametologue genes: Enhancing efficiency and cross-species applicability in kelp - Liping Liu; Zihan Gai; Yan Li; Yanling Liu; Shuxiu Chen; Xiaojie Li; Weiwei Wang; Linan Zhang (Aquaculture, 2026)

Experimental aerodynamic investigation of a suction sail model - Xinru Du; Jingpu Chen; Linan Guo; Yanxia Wang; Shiliang Hu; Hanfeng Wang; Xiyang Liu (Ocean Engineering, 2026)

Protective role of nano-selenium on Gymnocypris przewalskii under saline–alkaline stress: a comprehensive analysis of transcriptomics and metabolomics - Yanxia Chen; Zhaonan Li; Ying Yang; Tianxiu Liang; Shuchen Huang; Jingjing Zhang; Wenjie Jin; Linan Wang; Qingchun Yan; Changzhong Li (Fish Physiology and Biochemistry, 2026)

Whole-process ultrafast charge transfer for seconds-scale degradation in mineral processing wastewater: Piezo-phototronics effect on Ce-Fe dual active centers - Shuchen Tu; Chengyu Zhou; Tianyang Hao; Linghui Kuang; Hui Huang; Linan Xu; Tao Chen; Hongwei Huang; Bo Yan (Water Research, 2026)

Investigation of hydrate formation and flow characteristics within multiphase transmission pipelines employing a constant pressure visualization loop system - Xi Wang; Kaibang Liu; Shouyi Ma; Linan Guan; Zherui Chen; Yan Qin; Jingyue Sun; Cong Chen (Gas Science and Engineering, 2025)

Teleost HMGB1 paralogues mediate protective autophagy by interacting with NOD2 and ATG16L1 and activating ROS/Akt/mTOR pathway against Aeromonas hydrophila infection - Dan Wang; Linan Chen; Xiaoyu Ma; Zhe Wang; Hong Zhou (Fish & Shellfish Immunology, 2025)

Edwardsiella piscicida effector EseD mediates ferritinophagy by targeting NCOA4 and STING in teleost cells - Jingqi Ren; Linan Chen; Rong Ye; Dan Xiong; Zhe Wang; Hong Zhou (Fish & Shellfish Immunology, 2025)

Homologous nanocellulose modification: A “like cures like” strategy against coffee-ring and infiltration effects in paper-based colorimetric detection - Linan Sun; Yafei Lou; Siyu Chen; Hongyue Weng; Jiahao Li; Zhihui Lin; Junfei Tian; Rong Cao (Analytica Chimica Acta, 2025)

Naturally Occurring Epialleles and Their Roles in Response to Climate Change in Birch - Bowei Chen; Tianxu Zhang; Yile Guo; Lesheng Cao; Xu Zhang; Shahid Ali; Renyi Ma; Linan Xie; Jiang Wang; Gaurav Zinta; Shanwen Sun; Guifeng Liu; et al. (Molecular Ecology, 2025)
Epigenetics has been proposed to be an important mechanism that enables plant species to respond and adapt to environmental and climatic fluctuations and is sometimes entirely uncoupled from genetic variation. Nevertheless, the extent of this uncoupling and the contribution of epigenetics to plant responses to global climate change have not been well studied, particularly in forest trees. Here, we generated a high‐quality genome assembly for Betula platyphylla , a key pioneer species in temperate and boreal forest ecosystems, one of the most sensitive areas to global warming. Extensive multi‐omics sequencing of naturally white birch across the 48 provenances captured their full scope of temperate/boreal forests in Northeast China. Using a genome‐wide association study (GWAS), it was shown that over 55% of differentially methylated regions (DMRs) were spontaneous, independent of genetic factors. More than 30% of the spontaneous DMRs were significantly associated with gene expression, that is, potential epialleles, which are primarily involved in metabolism and responses to abiotic stresses; and 1819 of these epialleles were significantly associated with bio‐climatic variables (i.e., climatic epialleles, cEpialleles). Integrating these cEpialleles into a gradient modelling framework revealed that the natural populations of Asian white birch at high altitude/latitude might be most vulnerable to future climates. Our findings highlight the importance of integrating epigenomic and climatic data sets to forecast the adaptive capacity of a key forest species to rapid climate change.

Higginsianin F, one skeletal rearrangement diterpenoid α-pyridone with phytotoxic activity isolated from Colletotrichum higginsianum - Kang Chen; Kainan Song; Xiaoyang Hao; Chen Wang; Liwen Zhang; Qun Yue; Linan Xie; Yuquan Xu (Phytochemistry, 2025)

Combined semi-continuous feeding and stripping: Improving volatile fatty acid production and sulfate reduction in a two-phase anaerobic sulfate reduction system - Sifang Wang; Zerong Jiang; Linan Zhao; Kaoming Zhang; Ziyao Chen; Shilin Li; Yu Miao; Chun Hu; Zhu Wang (Environmental Research, 2025)

Polyploid breeding of Saccharina japonica: Harnessing aposporous reproduction - Pingping Tian; Yan Li; Nianchao Xue; Weiwei Wang; Shuxiu Chen; Yanling Liu; Juan Sun; Guangjin Liang; Juping Zhao; Liang Shi; Nan Zhao; Xia Li; et al. (Aquaculture, 2025)

Interface reaction constructs iron and phosphorus functionalized zeolite endowing EP with excellent fire safety and mechanical properties - Qihao Sun; Shanshan Chen; Xiaolong Chen; Linan Dun; Yuanhao Wang (Chemical Engineering Journal, 2025)

Potential bacterial resources for bioremediation of organochlorine pesticides and flame retardants recognized from forest soil across China - Jiayu Liu; Jialiang Kuang; Xiangwen Chen; Linan Huang; Zhenqing Shi (Journal of Hazardous Materials, 2025)

Achieving efficient water-electricity ensemble via using easily obtainable hydrovoltaic-thermoelectric hybrid generators - Jiacheng Hu; Jiangchao Huang; Yaxian Chen; Linan Xu; Bingquan Wu; Haotian Yue; Houqiang Ji; Haitao Li; Jian Jin (Desalination, 2025)

MagTFs: A tool for estimating multiple magnetic transfer functions to constrain Earth’s electrical conductivity structure - Zhengyong Ren; Zijun Zuo; Hongbo Yao; Chaojian Chen; Linan Xu; Jingtian Tang; Keke Zhang (Computers & Geosciences, 2025)

The quantity, reliability, transparency, reporting, and interpretation of pharmacovigilance signal detection studies in pregnancy: a meta-epidemiological study - Xue-Feng Jiao; Zhengyang Zhang; Lixiong Gong; Shan Lan; Songzhen Zhang; Jiang Wang; Xiubi Chen; Qiang Wei; Hailong Li; Linan Zeng; Lu Han; Lingli Zhang (European Journal of Clinical Pharmacology, 2025)

Silver and g-C3N4 co-modified biochar (Ag-CN@BC) for enhancing photocatalytic/PDS degradation of BPA: Role of carrier and photoelectric mechanism - Yaxuan Liu; Chen Yu; Huixia Lu; linan Liu; Jingchun Tang (Environmental Research, 2024)

Climate‐related naturally occurring epimutation and their roles in plant adaptation in A. thaliana - Bowei Chen; Min Wang; Yile Guo; Zihui Zhang; Wei Zhou; Lesheng Cao; Tianxu Zhang; Shahid Ali; Linan Xie; Yuhua Li; Gaurav Zinta; Shanwen Sun; et al. (Molecular Ecology, 2024)
DNA methylation has been proposed to be an important mechanism that allows plants to respond to their environments sometimes entirely uncoupled from genetic variation. To understand the genetic basis, biological functions and climatic relationships of DNA methylation at a population scale in Arabidopsis thaliana , we performed a genome‐wide association analysis with high‐quality single nucleotide polymorphisms (SNPs), and found that ~56% on average, especially in the CHH sequence context (71%), of the differentially methylated regions (DMRs) are not tagged by SNPs. Among them, a total of 3235 DMRs are significantly associated with gene expressions and potentially heritable. 655 of the 3235 DMRs are associated with climatic variables, and we experimentally verified one of them, HEI10 (HUMAN ENHANCER OF CELL INVASION NO.10). Such epigenetic loci could be subjected to natural selection thereby affecting plant adaptation, and would be expected to be an indicator of accessions at risk. We therefore incorporated these climate‐related DMRs into a gradient forest model, and found that the natural A. thaliana accessions in Southern Europe that may be most at risk under future climate change. Our findings highlight the importance of integrating DNA methylation that is independent of genetic variations, and climatic data to predict plants' vulnerability to future climate change.

Apomixis in Saccharina japonica: Parthenogenesis in male and apogamy in female gametophytes - Shutao Yue; Nianchao Xue; Cailing Yi; Juan Sun; Xia Li; Shuxiu Chen; Linan Zhang; Xiaojie Li (Aquaculture, 2024)

The divergence of DHN-derived melanin pathways in Metarhizium robertsii - Linan Xie; Yang Liu; Yujie Zhang; Kang Chen; Qun Yue; Chen Wang; Baoqing Dun; Yuquan Xu; Liwen Zhang (World Journal of Microbiology and Biotechnology, 2024)

Completely blocking the feminization by replacing Limnodilus spp. with Artemia salina to feeding XY Zig-zag eel (Mastacembelus armatus) - Baoyue Lu; Xiaowen Xue; Zhide Yu; Linan Zhang; Jinlin Yang; Yuwei Feng; Yiman Chen; Chong Han; Xiaoli Yin; Hu Shu (Aquaculture, 2024)

A novel and convenient zeolite modification strategy for enhancing the fire resistance of epoxy resin - Qihao Sun; Linan Dun; Xiaolong Chen; Shanshan Chen; Yuanhao Wang (Chemical Engineering Journal, 2024)

Use of statins and risks of ovarian, uterine, and cervical diseases: a cohort study in the UK Biobank - Xue-Feng Jiao; Hailong Li; Linan Zeng; Huazhen Yang; Yao Hu; Yuanyuan Qu; Wenwen Chen; Yajing Sun; Wei Zhang; Xiaoxi Zeng; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)
Purpose To examine the associations between use of statins and risks of various ovarian, uterine, and cervical diseases, including ovarian cancer, endometrial cancer, cervical cancer, ovarian cyst, polycystic ovarian syndrome, endometriosis, endometrial hyperplasia, endometrial polyp, and cervical polyp. Methods We conducted a cohort study among female participants in the UK Biobank. Information on the use of statins was collected through verbal interview. Outcome information was obtained by linking to national cancer registry data and hospital inpatient data. We used Cox proportional hazards regression to examine the associations. Results A total of 180,855 female participants (18,403 statin users and 162,452 non-users) were included. Use of statins was significantly associated with increased risks of cervical cancer (adjusted hazard ratio (HR), 1.55; 95% confidence interval (95% CI), 1.05–2.30) and polycystic ovarian syndrome (adjusted HR, 4.39; 95% CI, 1.68–11.49). However, we observed no significant association between use of statins and risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial hyperplasia, endometrial polyp, or cervical polyp. Conclusion Our findings suggest that use of statins is associated with increased risks of cervical cancer and polycystic ovarian syndrome, but is not associated with increased or decreased risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial polyp, or cervical polyp.

Revealing new insights: Two-center evidence of microplastics in human vitreous humor and their implications for ocular health - Yizhou Zhong; Yuhang Yang; Linan Zhang; Dahui Ma; Kailiang Wen; Jiachun Cai; Zhanmou Cai; Cui Wang; Xiaoyan Chai; Jingwen Zhong; Boxuan Liang; Yuji Huang; et al. (Science of The Total Environment, 2024)

The reference range of lamotrigine in the treatment of epilepsy in children: a systematic review - Jingjing Chen; Liang Huang; Linan Zeng; Zhimei Jiang; Meiping Xiong; Zhi-Jun Jia; Guo Cheng; Liyan Miao; Limei Zhao; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)
Purpose This study intends to assess the reference range of lamotrigine concentration for treating childhood epilepsy. Methods PubMed, Ovid-Embase, The Cochrane Library, CNKI, WanFang data and VIP databases were searched from database inception to January 2022. RCT, cohort study, case–control study, cross-sectional study that estimated the reference range of lamotrigine for children epilepsy treatment were included. The data extracted included basic information, statistical methods, data type, and results of reference range. Descriptive analysis was performed for them. Results 8 studies were included and estimated the reference range, and all of them were calculated based on efficacy data and/or concentration data. Statistical methods including ROC curve, concentration-effect curve, mean ± standard deviation, 95% confidence interval and percentile interval were utilized. For lamotrigine monotherapy, the lower limits ranged from 2.06 mg/L to 3.99 mg/L, and the upper limits ranged from 8.43 mg/L to 9.08 mg/L, showing basic consistency. However, for lamotrigine concomitant with valproate, the lower limits ranged from 2.00 mg/L to 8.00 mg/L, and the upper limit was 11.50 mg/L, for lamotrigine concomitant with other antiepileptics, the lower limits ranged from 1.00 mg/L to 3.09 mg/L, and the upper limits varied from 5.90 mg/L to 16.24 mg/L, indicating inconsistency. Conclusion Several studies have estimated the reference range of lamotrigine for childhood epilepsy, while controversy exist and no studies have determined the upper limit of the range based on safety data. To establish the optimal reference range, further high-quality studies are necessary that consider both efficacy and safety data.

Preferential role of distinct phytochemicals in biosynthesis and antibacterial activity of silver nanoparticles - Linan Liu; Chen Yu; Shakeel Ahmad; Cholnam Ri; Jingchun Tang (Journal of Environmental Management, 2023)

Design and preparation of lead-free (Bi0.4Na0.2K0.2Ba0.2)TiO3-Sr(Mg1/3Nb2/3)O3 high-entropy relaxor ceramics for dielectric energy storage - Bo Yan; Kepi Chen; Linan An (Chemical Engineering Journal, 2023)

Comparative genomic analysis of different virulence strains reveals reasons for the increased virulence of Aeromonas veronii - Bintong Yang; Chong Chen; Yufeng Sun; Linan Cao; Dongxing Zhang; Wuwen Sun; Lei Zhang; Guiqin Wang; Xiaofeng Shan; Yuanhuan Kang; Aidong Qian (Journal of Fish Diseases, 2021)
Aeromonas veronii is an important zoonotic and aquatic agent. More and more cases have shown that it has caused huge economic losses in the aquaculture industry in addition to threatening human health. But the reasons for the increasing virulence of A. veronii are still unclear. In order to further understand the reasons for the increased virulence of A. veronii , we conducted a comparative analysis of the genomes of A. veronii with different virulence. The analysis revealed that there are multiple virulence factors, such as those related to fimbriae, flagella, toxins, iron ion uptake systems and type II, type III and type VI secretion systems in the virulent strain TH0426 genome. And comparative analysis showed that there were two complete type III secretion systems (API1 and API2), of which the API2 and iron ion transport system were unique to the TH0426 strain. In addition, TH0426 strain also has unique functional gene clusters, which may play important roles in terms of resisting infection, adapting to different environments and genetic evolution. These particular virulence factors and gene clusters may be the important reasons for the increased virulence. These insights will provide a reference for the study of the pathogenesis of A. veronii .

Safety of azithromycin in pediatrics: a systematic review and meta-analysis - Linan Zeng; Peipei Xu; Imti Choonara; Zhenyan Bo; Xiangchen Pan; Wenyan Li; Xiaofeng Ni; Tao Xiong; Can Chen; Leshan Huang; Shamim Ahmad Qazi; Dezhi Mu; et al. (European Journal of Clinical Pharmacology, 2020)
Purpose To evaluate the toxicity of azithromycin in neonates, infants, and children. Methods A systematic review was performed for relevant studies using Medline (Ovid), PubMed, Cochrane Central Register of Controlled Trials, EMBASE, CINAHL, and International Pharmaceutical Abstracts. We calculated the pooled incidence of adverse drug reactions (ADRs) associated with azithromycin based on prospective studies (RCTs and prospective cohort studies) and analyzed the risk difference (RD) of ADRs between azithromycin and placebo or other antibiotics using meta-analysis of RCTs. Results We included 133 studies with 4243 ADRs reported in 197,675 neonates, infants, and children who received azithromycin. The safety of azithromycin as MDA in pediatrics was poorly monitored. The main ADRs were diarrhea and vomiting. In prospective non-MDA studies, the most common toxicity was gastrointestinal ADRs (938/1967; 47.7%). The most serious toxicities were cardiac (prolonged QT or irregular heart beat) and idiopathic hypertrophic pyloric stenosis (IHPS). Compared with placebo, azithromycin did not show increased risk ADRs based on RCTs (risk difference − 0.17 to 0.07). The incidence of QT prolonged was higher in the medium-dosage group (10–30 mg/kg/day) than that of low-dosage group (≤ 10 mg/kg/day) (82.0% vs 1.2%). Conclusion The safety of azithromycin as MDA needs further evaluation. The most common ADRs are diarrhea and vomiting. The risk of the most serious uncommon ADRs (cardiac-prolonged QT and IHPS) is unknown.

Characteristics of indoor and outdoor fine particles in heating period at urban, suburban, and rural sites in Harbin, China - Wenxu Fang; Weiwei Song; Liyan Liu; Guangnian Chen; Linan Ma; Yuxuan Liang; Yujie Xu; Xueying Wang; Yehao Ji; Yu Zhuang; Amadou Hima Boubacar; Yifan Li (Environmental Science and Pollution Research, 2020)

Halorubrum depositum sp. nov., a Novel Halophilic Archaeon Isolated from a Salt Deposit - Shaoxing Chen; Siqi Sun; Yao Xu; Jinting Lv; Linan Chen; Liu Liu (Current Microbiology, 2018)

The Functional and Molecular Properties, Physiological Functions, and Pathophysiological Roles of GluN2A in the Central Nervous System - Yongjun Sun; Xiaokun Cheng; Linan Zhang; Jie Hu; You chen; Liying Zhan; Zibin Gao (Molecular Neurobiology, 2017)